Morphological diversity and genetic structure within Lerista kalumburu Storr, 1976 (Squamata: Scincomorpha: Sphenomorphidae)—taxonomic implications - Amey, Andrew P.; Wilmer, Jessica Worthington (Zootaxa, 2014)
Discovery of a population of two-toed Lerista allied to L. kalumburu prompted a morphological and genetic examination of this taxon.  Molecular analysis showed limited divergence and paraphyly of three-toed populations with respect to the two-toed form.  We contend that these populations are best viewed as a single species exhibiting remarkable diversity in limb morphology.  As this prevents successfully identifying the taxon using published keys, we provide a new diagnosis and a redescription of the species.